Vedolizumab for inflammatory bowel diseasesI - Igor L. Khalif; M. V. Shapina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of review. To present literature data on administration of vedolizumab at inflammatory bowel diseases. Summary. The vedolizumab is anti-α4β7-integrin humanized class IgG1 antibodies which suppresses migration of leukocytes in intestinal tissue, interfering thereby with development of pathologic inflammation. GEMINI-1 study of ulcerative colitis has demonstrated efficacy of the drug in remission induction (clinical response rate of 47,1% of patients, clinical remission of 16,9% and endoscopic remission of 40,9% at the 6th week) and in remission maintenance (percent of patients in clinical remission at 52nd week at drug injection every 4 weeks - 44,8%). Similar efficacy was demonstrated for Crohn's disease (GEMINI-2) study in remission induction (clinical response rate - 31,4% of patients, clinical remission - 14,5%) and remission maintenance (percentage of patient in clinical remission by 52nd week at injection of the drug every 4 weeks - 39%). The results received in clinical trials were confirmed by clinical data in the different countries. Safety profile investigations demonstrated low system immune suppression due to specific action mechanism of the drug. Besides, due to α4β7 integrin heterodimer selectivity of vedolizumab, it provides selective block of intestinal leukocyte migration, without affection of central nervous system therefore the risk of the progressing multifocal leukoencephalopathy is not established. Conclusion. Present clinical trials has demonstrated that vedolizumab is effective and safe in treatment of inflammatory bowel diseases.